2011
DOI: 10.1098/rspb.2011.1023
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic performance of a hovering hawkmoth with flexible wings: a computational approach

Abstract: Insect wings are deformable structures that change shape passively and dynamically owing to inertial and aerodynamic forces during flight. It is still unclear how the three-dimensional and passive change of wing kinematics owing to inherent wing flexibility contributes to unsteady aerodynamics and energetics in insect flapping flight. Here, we perform a systematic fluid-structure interaction based analysis on the aerodynamic performance of a hovering hawkmoth, Manduca, with an integrated computational model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
142
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(149 citation statements)
references
References 41 publications
(78 reference statements)
7
142
0
Order By: Relevance
“…10 4 for the flycatcher's wing tip section (electronic supplementary material, table S2) we would expect the LEV to burst and separate from the hand wing before the end of the downstroke [13,14], as was found in a birdinspired flapper at similar l ds % p/(2k) ¼ 5.2, where k is reduced frequency [11]. The fact that this does not occur in the flycatcher could be owing to the relatively low a eff at the wingtip section (figure 2b), since in a computational model of a flapping insect wing, LEV bursting near the wing tip was delayed owing to flexible wing twisting [23]. Also, a mechanical insect wing model operating at comparable flow conditions did not suffer from LEV bursting when a eff was reduced below a critical value [14].…”
Section: Discussionmentioning
confidence: 90%
“…10 4 for the flycatcher's wing tip section (electronic supplementary material, table S2) we would expect the LEV to burst and separate from the hand wing before the end of the downstroke [13,14], as was found in a birdinspired flapper at similar l ds % p/(2k) ¼ 5.2, where k is reduced frequency [11]. The fact that this does not occur in the flycatcher could be owing to the relatively low a eff at the wingtip section (figure 2b), since in a computational model of a flapping insect wing, LEV bursting near the wing tip was delayed owing to flexible wing twisting [23]. Also, a mechanical insect wing model operating at comparable flow conditions did not suffer from LEV bursting when a eff was reduced below a critical value [14].…”
Section: Discussionmentioning
confidence: 90%
“…These small insect flyers have flexible wings that experience large deformations just like birds and bats [11,12]. It has been, for example, shown that wing deformations [13,14] can enhance the force generation and efficiency of a locust operating at Re % 4 Â 10 3 [13], or a hawkmoth at Re % 6.3 Â 10 3 [15]. Moreover, several studies have suggested that insect wing rotations may be passive [16,17], meaning that the resulting rotation is due to a dynamic balance between the wing inertial force, elastic restoring force and fluid dynamic force.…”
Section: Introductionmentioning
confidence: 99%
“…Research on heterogeneous wings has appeared more recently [85,64,63,82,17,48,47,66]. The majority of these studies focus on insect flight and, more specifically, simulating the coupled aeroelastic dynamics of compositionally complex wings [64,63,82,66].…”
Section: Introductionmentioning
confidence: 99%